Pengaruh Kemandirian Belajar Terhadap Prestasi Belajar Matematika Siswa - Somawati (Universitas Sarjanawiyata Tamansiswa, 2022)
The purpose of this study is to know empirically about the relationship of learning independence to student learning achievement. The method used in this study is the survai method. The sample used in this study as many as 40 students using probability sampling devoted to simple random sampling. This study has a reliability coefficient of 0.841 so that the instrument is declared reliable. The hypothesis of this study is that there is a significant relationship between student learning independence and student learning achievement. Before hypothesis testing is first done testing the prerequisites of analysis using the liliefors test for the normality test. At the signification level of 0.05 with the liliefors test obtained L0 = 0.1194 and Ltable = 0.1401 (L0 < Ltable), then the study distributed normally. Regression signification test at signification level 0.05 is obtained Fcount 0.62 while Ftable 2.19 in other words accept H0 and linear pattern regression model. Hypothesis testing with a t test with a significant level of 0.05. From the results of the calculation obtained tcount 2.16 whereas ttable 2,042 (2.16 > 2,042). Therefore, H0 rejected and H1 accepted. The study concluded that there’s a big influence between learning independence on students' learning achievement.